The ability of mouthguards to protect veneered teeth: A 3D finite element analysis - Dal Piva, Amanda Maria O.; Tribst, João Paulo Mendes; Borges, Alexandre Luiz S. [UNESP]; Kleverlaan, Cornelis J.; Feilzer, Albert J. (Wiley, 2023)
Background/Aims: Professional and amateur athletes might have veneer restorations. The aim of this study was to investigate the protective effect of mouthguards on veneered anterior restorations. Methods: A nonlinear dynamic analysis was performed to simulate conditions during an impact with or without a custom-made mouthguard. Using a computer-aided design (CAD) software, a slice of a human maxilla was designed containing an upper right central incisor. The model was composed of mucosa, cortical bone, trabecular bone, periodontal ligament, dentin, enamel, and pulp tissue. The enamel was prepared (feather design), restored with an indirect veneer (1.0 mm thickness), and duplicated to simulate both conditions with or without a mouthguard (4 mm thickness). Both models were subdivided into finite elements using the computer-aided engineering (CAE) software. Frictionless contacts were used, and an impact was simulated in which a rigid sphere hit the model at 1 m s−1. Fixation was defined at the base of the bone. The elastic modulus of the veneer was assessed by using five different restorative materials (resin composite, hybrid ceramic, zirconia-reinforced lithium silicate, lithium disilicate, and zirconia). Von Mises stress, minimal principal stress, and maximum principal stress (in MPa) were obtained and plotted for visual comparison. Results: Von-Mises results showed higher stress concentrations in the veneer's cervical labial region for models without a mouthguard. Observing the quantitative results for each model, the highest compressive (709 MPa) and tensile (58 MPa) stresses occurred in the situation without a mouthguard with a zirconia veneer, while the lowest occurred in resin composite veneer with a mouthguard (8 and 5 MPa). The mouthguard was able to reduce the stresses in the tooth structure and it also reduced the risk of fracture in all conditions. Conclusions: Mouthguards were beneficial in reducing the effects of dental trauma regardless of the restorative material used to manufacture the indirect veneer, since they act by dampening the generated stresses during the trauma event. Equal impact stresses on a mouthguard will lead to higher stresses in veneered teeth with more rigid restorative materials leading to a less protective effect.
Keywords: contact sports; dental trauma; mouthguard; prevention; tooth injury